1962
DOI: 10.1084/jem.115.4.821
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity to Penicillenic Acid Derivatives in Human Beings With Penicillin Allergy

Abstract: In this paper we are concerned with the following question: Are the benzylpenicilloyl and the benzylpenicillenate groups specific determinants of allergic reactions to benzylpenicillin in man? 1 Since simple organic molecules combine covalently with proteins as a preliminary step in the induction of the hypersensitive state, it seems clear that penicillin itself, which is incapable of reacting in the required manner with protein, must be regarded as a precursor of some derivative which possesses this necessary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
0
13

Year Published

1962
1962
1988
1988

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(77 citation statements)
references
References 11 publications
1
63
0
13
Order By: Relevance
“…The materials were nonirritating as used. Previous studies showed these reagents and the 2 IgG antibodies are 7 S (molecular weight about 160,-000), and IgM antibodies are 19 S (molecular weight about 1,000,000). Skin-sensitizing antibodies appear to be neither IgM nor IgG antibodies.…”
Section: Methodsmentioning
confidence: 94%
“…The materials were nonirritating as used. Previous studies showed these reagents and the 2 IgG antibodies are 7 S (molecular weight about 160,-000), and IgM antibodies are 19 S (molecular weight about 1,000,000). Skin-sensitizing antibodies appear to be neither IgM nor IgG antibodies.…”
Section: Methodsmentioning
confidence: 94%
“…On the evidence presented, the role of a high degree of conjugation decreasing antigenicity might also explain the absence of immune response observed by these investigators. The antigenicity in guinea pigs of DNP conjugates of polylysine averaging only 20 lysyl residues warrants caution in the use of such polymers conjugated with benzyl penicilloyl in human penicillin sensitivity studies as it has been suggested (25).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, many authors have long suspected BPO groups to be involved in the pathogenesis of penicillin allergy (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%